Transfer of Party in The Agreement May Void the Agreement as A New Today of Law in Indonesia - Ahmad Yulianto; Athari Farhani (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
The ratification of Law No.7 of 1989 concerning the Religious Courts brought enormous changes to the position of the religious judiciary, not only in its position as a judicial institution as part of executing the same judicial power as other judicial institutions. However, the ratification of the granting of full authority which is the main task of the religious court to resolve cases of Muslims in Indonesia relating to family law. With the birth of the religious court law, the religious judiciary has become independent in Indonesia in enforcing laws based on Islamic law for those seeking justice who are Muslim in relation to civil matters in the fields of marriage, inheritance, wills, grants and endowments. Therefore, Muslims in Indonesia are required to submit their cases to the religious court which is the authority of the religious court. Jurisprudence is a fundamental need to complement various laws and regulations in the application of law because in the national legal system it plays a role as a source of law. Without jurisprudence, the function and authority of the judiciary as the executor of judicial power will cause sterility and stagnation. Jurisprudence aims to keep laws up to date and apply effectively, and can even increase the authority of the judiciary because they are able to maintain legal certainty, social justice and protection. Legal certainty will be realized if in the application of law there is a common perception. The existence of legal certainty will prevent or avoid disparities and inconsistencies in decisions because judges have applied the same legal standards to cases or cases that are the same or similar to cases that have been terminated or tried by a previous judge, so that the verdict on his case can be predicted by justice seekers. With this consistent decision, a sense of justice and legal certainty can be realized.